Loss in services precedes high school exit for teens with autism spectrum disorder: A longitudinal study. Issue 6 (29th April 2019) - Laxman, Daniel J.; Taylor, Julie Lounds; DaWalt, Leann S.; Greenberg, Jan S.; Mailick, Marsha R.
Abstract : The present longitudinal study investigated changes in service receipt and unmet service needs spanning 14 years before and after high school exit in a large community‐based sample of individuals with autism spectrum disorder (ASD) ( n  = 204), of whom 59% had co‐occurring intellectual disability (ID). Using multilevel models, potential discontinuity of service patterns at the point of high school exit was examined, as well as the rate of change in services received and needed during the high school years and into the post‐high school period. Differences between those with and without ID were probed. Study findings indicated that overall, sample members experienced a reduction in receipt of services during high school, particularly for those without co‐occurring ID. After high school exit, sample members experienced a decline in services received; for those without ID, there was a continuous rate of loss of services after leaving high school but for those with ID, there was a sharp decline in services received. Unmet service needs increased right after high school exit for both those with and without ID. These patterns reflect loss of entitlement for services that accompanies high school exit, and the limited availability of adult services for individuals with ASD. This study documented not only the post‐high school service cliff that has been the subject of much concern, but also that the loss of services begins long before high school exit and that subgroups of the population with ASD are particularly vulnerable. Autism Res 2019, 12: 911–921 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: In this research, we studied changes in the number of services received before and after high school exit in a large sample of individuals with autism spectrum disorder (ASD). With each passing year during high school, individuals with ASD received fewer services. At the time of high school exit, there was a sharp drop in the number of services received, particularly for those with co‐occurring intellectual disability. This study found not only that there is a post‐high school service cliff, but also that the loss of services begins long before high school exit.